A new multidimensional questionnaire to assess awareness of age-related change (AARC) - Brothers, Allyson; Gabrian, Martina; Wahl, Hans-Werner (The gerontologist, 2019)
This two-study article describes the development and evaluation of a multidimensional questionnaire based on the subjective aging construct Awareness of Age-Related Change (AARC). AARC captures the inherent multidimensionality and complexity of aging attitudes, which are strongly linked to indicators of successful aging, including health and well-being.